Diagnostics and Features of Forming Corporate Culture of Students in University Educational Environment - BROVKO, Ekaterina; ZAGORODNYA, Alla; SHAHEID ANAD, Ali; TERNOPOLSKAYA, Valentyna; CHERNUKHA, Nadezhda (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article diagnoses the formation of the corporate culture of the students of the Kyiv Municipal Pedagogical University and Uman State University. Such diagnoses reveal the students' level of knowledge about the nature and the substantive aspects of the culture and attitude of the individual. The concept of the individual's corporate culture, its structure, criteria and indicators are defined.RESUMEN El artículo diagnostica la formación de la cultura corporativa de los estudiantes de las universidades Kyiv Municipal Pedagogical University y Uman State University. Dichos diagnósticos revelan el nivel de conocimiento de los estudiantes sobre la naturaleza y los aspectos sustantivos de la cultura y actitud del individuo. Se define el concepto de la cultura corporativa del individuo, su estructura, criterios e indicadores.